2014
DOI: 10.1061/(asce)gm.1943-5622.0000264
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Fresh and Fouled Railway Ballast Subjected to Direct Shear Testing: Discrete Element Simulation

Abstract: This paper presents the three-dimensional discrete element method (DEM) that was used to study the shear behaviour of fresh and coal fouled ballast in direct shear testing. The volumetric changes and stress-strain behaviour of fresh and fouled ballast were simulated and compared with the experimental results. 'Clump logic' in Particle Flow Code (PFC3D) incorporated in a MATLAB Code was used to simulate irregular shaped particles in which groups of ten to twenty spherical balls were clumped together in appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 42 publications
(52 reference statements)
8
104
0
Order By: Relevance
“…Nevertheless, the current DEM analysis was limited to the linear contact model to reduce the computation time, and therefore the damping ratio was not required . The micromechanical parameters used in this study to model ballast were adopted from Indraratna et al (2014) since the same ballast material was tested (i.e. latite basalt, collected from the Bombo quarry near the city of Wollongong).…”
Section: Discrete Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the current DEM analysis was limited to the linear contact model to reduce the computation time, and therefore the damping ratio was not required . The micromechanical parameters used in this study to model ballast were adopted from Indraratna et al (2014) since the same ballast material was tested (i.e. latite basalt, collected from the Bombo quarry near the city of Wollongong).…”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…Huang and Tutumluer (2011) used DEM to simulate fouled ballast under direct shear test conditions and reported that fouling is a critical agent that could affect particle interaction and cause the track to become distressed. Indraratna et al (2014) used DEM to model direct shear tests for coal-fouled ballast and showed that coal fines would reduce the shear strength of fouled ballast. They observed that miniature particles (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…First was published in [9] and the dimensions of a large scale shear box (Fig. 7) were a = 300 mm, b = 300 mm, and c = d = 100 mm.…”
Section: Shear Testmentioning
confidence: 99%
“…The discrete element method (DEM) that was introduced by Cundall and Strack [15] has been widely used to simulate granular materials [16][17][18][19], but the application of DEM to study the behaviour of fouled ballast and analyse its interface mechanism with the reinforcing geogrid is limited. Several multi-layer track models have been developed to analyse the inherent stresses and deformations in all the major components of track and subgrade, i.e., the rails, fasteners, sleepers, ballast, sub-ballast, and subgrade [20][21][22], but they all assume an elastic behaviour for the track layers, including the ballast.…”
Section: Introductionmentioning
confidence: 99%